Frequency of Oral Lesions in Patients with HIV/AIDS in Sari, Iran - Tahereh Molania; Mohsen Aarabi; Jamshid Yazdani Charati; Haleh Hali; Mohammad Reza Parsaei; Fatemeh Daneshvar; Fatemeh Bozorgnia; Fatemeh Sadeghi; Maedeh Salehi (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Oral manifestations and their prevalence are of great importance in patients with HIV infection due to their diagnostic value and role on prognosis and monitoring patients’ immunity. All these influence patients' quality of life. The goal of this study was to investigate oral manifestations in patients with HIV/AIDS infection. Materials and methods: This descriptive-cross sectional study was conducted in patients attending counseling center for behavioral diseases in Sari, Iran 2019. Data analysis was done in SPSS V25. Results: Oral manifestations were observed in the majority of patients (96%) ranging from one to six oral lesions.  The most common lesions were coated tongue (80.4%), mucosal hyper pigmentation (38.9%), periodontitis (26.8%), frictional hyper keratosis and fissure tongue (24.3%), and gingivitis and erythomatous candidiasis (19.5%). Conclusion: In this study, the prevalence of oral lesions in patients with HIV/AIDS was relatively low, but there were poor periodontal conditions. Hence, appropriate oral hygiene, providing high quality dental services, and prosthodontic care are needed in these patients.